MENINGKATKAN HASIL BELAJAR MATEMATIKA DENGAN PENERAPAN METODE DEMONSTRASI SISWA KELAS V SD NEGERI 009 AIR EMAS KECAMATAN UKUI - Tugino (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The background of this study is the low mathematics learning outcomes of fifth-grade students at SD Negeri 009 Air Emas. This study aims to improve learning outcomes by applying the mathematical demonstration method. This research is classroom action research conducted over two cycles. The data used in this study are students’ learning outcome data. The results show an improvement in student learning outcomes, as evidenced by the increase in learning completeness: initially, only 50% of students achieved learning completeness; after improvements in the first cycle, this increased to 70%; and in the second cycle, it further increased to 85%.